1991
DOI: 10.1042/bst019411s
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibitory effects of lithium and magnesium on longitudinal smooth muscle contraction

Abstract: Biochemical SocietyTransactions (1 991) 19 41 1 S Comparison of inhibitory effects of lithium and magnesium on longitudinal smooth muscle contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…We have shown that magnesium ( 2 3 . 8 m M ) significantly reduced the maximal contraction responses to carbachol (CCh) in the rat jejunum and ileum and in the colon and stomach fundus there was an inhibition which was, however, not significantly different from control [ 2 ] .…”
mentioning
confidence: 85%
“…We have shown that magnesium ( 2 3 . 8 m M ) significantly reduced the maximal contraction responses to carbachol (CCh) in the rat jejunum and ileum and in the colon and stomach fundus there was an inhibition which was, however, not significantly different from control [ 2 ] .…”
mentioning
confidence: 85%